2009
DOI: 10.1021/la902564n
|View full text |Cite
|
Sign up to set email alerts
|

Enzyme-Mediated Assimilation of DNA-Functionalized Single-Walled Carbon Nanotubes

Abstract: When pyrimidine-functionalized carbon nanotubes were incubated with single-stranded DNA ligase, formations of macroscopic aggregates were observed. Wet-cell transmission electron microscopy imaging revealed that the nanotubes were radially bound to form a 3D latticelike structure. These structures were not observed in control reactions lacking ligase or adenosine triphosphate. Raman spectroscopy analysis revealed no spectra indicative of carbon nanotubes in ligase-unamended controls; however, spectra were obse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 20 publications
0
9
1
Order By: Relevance
“…Microscopic techniques are also powerful tools to directly characterize DNA-CNT hybrids [ 56 , 83 , 98 , 99 , 113 , 116 , 117 , 118 , 119 , 120 , 121 , 122 , 123 , 124 , 125 , 126 ]. Although TEM and SEM are major techniques, they are too broad to be adequately summarized in this section.…”
Section: Characterization Of Dna-cnt Hybridsmentioning
confidence: 99%
See 1 more Smart Citation
“…Microscopic techniques are also powerful tools to directly characterize DNA-CNT hybrids [ 56 , 83 , 98 , 99 , 113 , 116 , 117 , 118 , 119 , 120 , 121 , 122 , 123 , 124 , 125 , 126 ]. Although TEM and SEM are major techniques, they are too broad to be adequately summarized in this section.…”
Section: Characterization Of Dna-cnt Hybridsmentioning
confidence: 99%
“…The study demonstrated that the surface potential against Au substrate varied depending on the type of SWNTs. Arnett et al reacted ssDNA ligase with DNA-CNT hybrids that were prepared with pyrimidine-functionalized CNTs and observed the formation of a 3D lattice-like CNT structure using wet-cell TEM [ 120 ]. Hayashida et al performed Kelvin force microscopy to measure the surface potential of ssDNA-SWNT hybrids and other related samples [ 121 ].…”
Section: Characterization Of Dna-cnt Hybridsmentioning
confidence: 99%
“…Higher gene expressions (5-10 times) have been observed in cells containing CNTs compared to those without nanotubes. Recent studies have shown that pyrimidine functionalized CNTs incubated with single-stranded DNA formed macroscopic aggregates that were radially bound to form a 3D lattice structure, as seen in Figure 9 (28, 29). DNA was used to effectively disperse and separate bundled SWCNTs in water (28).…”
Section: Methods Of Functionalizing Cntsmentioning
confidence: 99%
“…Recent studies have shown that pyrimidine functionalized CNTs incubated with single-stranded DNA formed macroscopic aggregates that were radially bound to form a 3D lattice structure, as seen in Figure 9 (28, 29). DNA was used to effectively disperse and separate bundled SWCNTs in water (28). Based on molecular modeling studies, it was suggested that single-stranded DNA could bind to CNTs through π-stacking, resulting in helical wrapping on the surface.…”
Section: Methods Of Functionalizing Cntsmentioning
confidence: 99%
“…Many researchers observed 3D structures of CNTs by AFM, and diverse lengths and widths of various types of CNT nanobioconjugates have been reported [ 69 , 241 252 ]. Biochemical reactions, such as the interaction between protein and DNA molecules on CNT surfaces, were studied by AFM and other scanning techniques [ 232 , 245 , 253 264 ].…”
Section: Structures and Mechanical Properties Studied By Afmmentioning
confidence: 99%